Heavy metals (Cr, Cu, Pb, and Zn) concentrations of road-deposited sediments along bridges in Iloilo City. - Gastar, Abraham N.
An increasing usage of motored vehicles in modern mode of land transportation has an impact to the distribution of certain heavy metals in the environment. Cr, Cu, Pb, and Zn are some of the heavy metals known to be associated with motored vehicle acitvities. Road-deposited sediment samples were collected from four bridges (Forbes Bridge, Iloilo Bridge, Jalandoni Bridge, and Quirino-Lopez Bridge) in Iloilo City during October (2009) and January (2010). The road-deposited sediments were treated with 0.5 M HCl for digestion and Cr, Cu, Pb, and Zn concentrations were determined using Flame Atomic Absorption Spectrophotometer (FAAS). The mean concentrations of Cr, Cu, Pb, and Zn in sediments for all bridge sites were 4.46 +- 1.0, 36.46 +- 20.99, 57.86 +- 38.40, and 132 +- 42.37 mg/kg, respectively. A general increase of heavy metals concntration was observed from October (2009) to january (2010). Cr, Cu, Pb, and Zn enrichment in road-deposited sediments was around x1, x7, x6, and x14 more respectively, as compared to the background control levels. Road-deposited sediments collected from Forbes Bridge had a significant increase in temporal variation for all heavy metals determined. A significant correlation was observed between Cr and Zn, and Cu and Pb indicating similar sources. High positive coerrlations (R2 = 0.650 - 0.915) were also observed between heavy metals concentrations and the number of vehicles per hour passing through the bridges. Over-all, road-deposited sediments deposited along bridge sidewalks in Iloilo Cit have low to moderate potential ecological risk levels.